High Normal Urinary Albumin–Creatinine Ratio Is Associated With Hypertension, Type 2 Diabetes Mellitus, HTN With T2DM, Dyslipidemia, and Cardiovascular Diseases in the Chinese Population: A Report From the REACTION Study - Wang, Jie; Wang, Yun; Li, Yijun; Hu, Ying; Jin, Lingzi; Wang, Weiqing; Gao, Zhengnan; Tang, Xulei; Yan, Li; Wan, Qin; Luo, Zuojie; Qin, Guijun; et al. (Frontiers in Endocrinology, 2022)
Background Albuminuria has been widely considered a risk factor for cardiovascular diseases (CVDs), which is associated with hypertension (HTN), type 2 diabetes mellitus (T2DM), HTN with T2DM, and dyslipidemia. However, the associations between albuminuria and HTN, T2DM, HTN with T2DM, dyslipidemia, and CVDs are still unclear. Thus, this study aimed to explore the association of albuminuria thoroughly, especially within the normal range, with the abovementioned diseases in the Chinese population. Methods This study included 40,188 participants aged over 40 years from seven centers across China. Urinary albumin–creatinine ratio (UACR) was firstly divided into the ≥30-mg/g group, indicating kidney damage, and <30-mg/g group. Furthermore, UACR was divided into five groups: the <20%, 20%–39%, 40%–59%, 60%–79%, and ≥80% groups, according to the quintile division of participants within the normal range. Propensity score matching was used to reduce bias, and multiple logistic regression models were conducted to examine the association between UACR and HTN, T2DM, HTN with T2DM, dyslipidemia, and CVDs. Results Multivariable regression analysis revealed that UACR, even within the normal range, is significantly associated with HTN, T2DM, HTN with T2DM, dyslipidemia, and CVDs, and the association between UACR and HTN with T2DM was the most significant in model 3 even after adjusting for confounding factors (HTN: OR = 1.56 (95% CI = 1.45–1.68), p < 0.0001; T2DM: OR = 1.78 (95% CI = 1.60–1.97), p < 0.0001; HTN with T2DM: OR = 1.76 (95% CI = 1.59–1.95), p < 0.0001; dyslipidemia: OR = 1.08 (95% CI = 1.01–1.14), p = 0.0146; CVDs: OR = 1.12 (95% CI = 1.00–1.25), p = 0.0475). In the stratified analysis, high normal UACR was significantly associated with HTN, T2DM, HTN with T2DM, and dyslipidemia in subgroups. Conclusions In summary, we observe a higher prevalence of HTN, T2DM, HTN with T2DM, dyslipidemia, and CVDs in abnormal UACR and reveal a significant association of UACR, even within the normal range, with HTN, T2DM, HTN with T2DM, dyslipidemia, and CVDs.